Antioxidant potential of lettuce treated by Thymol as an allochemical - Seyed Mehdi Razavi; Parisa Nesrollahi; Alireza Ghasemian (Open Journal of Biological Sciences - Peertechz Publications, 2017)
Introduction: Thymol is a phenolic compound with monoterpenes nature (C10H14O) which is one of the main secondary metabolites of the genus of Thymus in Lamiaceae family. Methods: In this study, antioxidant capability changes, antioxidant compounds level and the total free amino acids of Lettuce were investigated under different levels of Thymol (0.0 and 0.05 mg/ml) treatment. Results: The results showed that the amount of fl avonoids and anthocyanins had drastic decrease with increase of Thymol. The decrease was 15% and 14% in comparison with control group, respectively. On the other hand, the amount of free amino acids increased by 26.47% increase. Antioxidant capacity of lettuce exhibited a drastic reduction under treatment with Thymol, this reduction was 645% than control. Conclusion: It was concluded that thymol, as an allochemical can be tend to reduce antioxidant potential of lettuce.